2004
DOI: 10.1097/00000542-200407000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perioperative Central Neuraxial Analgesia on Outcome after Coronary Artery Bypass Surgery

Abstract: There were no differences in the rates of mortality or myocardial infarction after coronary artery bypass grafting with central neuraxial analgesia. There were associated improvements in faster time until tracheal extubation, decreased pulmonary complications and cardiac dysrhythmias, and reduced pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
130
1
18

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(159 citation statements)
references
References 46 publications
10
130
1
18
Order By: Relevance
“…However, there have been conflicting reports regarding the effects of TEA on postoperative pulmonary function and atelectasis. [3][4][5][6] A recent meta-analysis by Liu et al 12 with a combined total of 1,178 patients, found that TEA decreased the incidence of pulmonary complications. in the present study, TEA was associated with a significant improvement in pulmonary function during the first two postoperative days, using FEV 1 as a surrogate for pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been conflicting reports regarding the effects of TEA on postoperative pulmonary function and atelectasis. [3][4][5][6] A recent meta-analysis by Liu et al 12 with a combined total of 1,178 patients, found that TEA decreased the incidence of pulmonary complications. in the present study, TEA was associated with a significant improvement in pulmonary function during the first two postoperative days, using FEV 1 as a surrogate for pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…12 On the other hand, a recent meta-analysis including 1178 patients found that although TEA is associated with shorter time until tracheal intubation and decreased pulmonary complications and cardiac arrhythmias, no effect on mortality or rates of myocardial infarction could be found. 30 However, most of the studies included in this meta-analysis were small (Յ50 treated patients), and because the pooled mortality rate of the study was low, the authors concluded that more larger-scale randomized controlled trials are required to fully assess the potential benefits of TEA for the reduction of myocardial infarction and mortality after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A recently-published meta-analysis provides some perspective. 8 These authors, via Medline and other databases, searched for randomized controlled trials in patients undergoing coronary artery bypass surgery with cardiopulmonary bypass. Fifteen trials enrolling 1,178 patients were included for thoracic epidural analysis and 17 trials enrolling 668 patients were included for intrathecal analysis.…”
mentioning
confidence: 99%
“…1,2 Une méta-analyse, publiée récemment, fournit une certaine perspective. 8 Les auteurs ont utilisé, entre autres, la base Medline pour chercher des essais randomisés et contrôlés auprès de patients devant subir un pontage aortocoronarien avec circulation extracorporelle. Quinze essais comprenant 1 178 patients ont été inclus pour analyse de l'anesthésie péridurale thoracique et 17 essais auprès de 668 patients pour analyse de l'anesthésie intrathécale.…”
unclassified